Are you as safe at a concert or Music Festival as you think you are? - Sonnen, KT (Cranfield University, 2024)
Poster contribution to the Defence and Security Doctoral Symposium 2023
Keywords: Safety; Security; Terrorism perception; Music; Concert; Event; festival; DSDS23; DSDS23 Poster